Antifungal Activities of Selected Plant Extracts in In-Vitro Control of Anthracnose and Root Rot Diseases on Cucumber (Cucumis sativus B.) - Ogundipe, Wuraola Funmi; Pitan, Ayotunde Ajoke; Adedire, Oluwafemi Michael; Farinu, Adekunle Opeyemi; Oyewole, Barry Oyeyemi (International Journal of Sustainable Agricultural Research, 2021)
An in-vitro experiment was conducted at National Centre for Genetic Resources and Biotechnology and the Nigeria Agricultural Quarantine Service, Moor plantation, Ibadan. The experiment was carried out to test the antifungal efficacy of some plant extracts (Ageratum conyzoides, Azadirachta indica, Morinda lucida, and Chromolaena odorata) and a chemical fungicide (mancozeb). The mycelial growth inhibition potentials of five concentrations of aqueous plant extracts were assayed at different incubation periods on the growth of Colletotrichum orbiculare and Lasiodiplodia theobromae. The experiment was carried out in a Completely Randomized Design (CRD) with five replications. A 3 mm mycelial disc of each test fungus was placed at the center of a 9 cm Petri dish containing 5, 10, 15, 20, and 25 g of the plant extracts or 0.25g/100mL of mancozeb (synthetic fungicide) in Potato Dextrose Agar. The results obtained revealed that all the plant extracts, at all concentrations, significantly inhibited the growth of these mycopathogens, with 25g C. odorata having the highest percentage inhibition of 70.78% and 73.68% at 48 and 96 hours of incubation on C. orbiculare and L. theobromae respectively. All the selected aqueous extracts inhibited more than 50% C. orbiculare mycelial growth. Antifungal extracts recovered from the selected plants could be further purified to improve and characterize their fungicidal activities in controlling plant diseases. Extracts of plant materials, which are readily available to the farmers, are better alternatives to the commonly used hazardous, synthetic fungicides.